IMMUNONUTRITION WITH GLUTAMINE IN ICU PATIENTS - Das, Rekha; Routray, Sidharth Sraban; Pradhan, Amit; Ipsita, Snigdha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Endogenous production of glutamine may be reduced during critical illness. The shortage of glutamine is reflected as a decrease in plasma concentration, which is a prognostic factor for outcome in sepsis. Therefore, we have studied the effect of enteral or parenteral glutamine therapy on biochemical parameters and the hospital stay of critically ill patients. Methods: A total of 66 critically ill patients aged 18-70 years, admitted to central and medical intensive care unit of a tertiary care hospital were randomly divided into three equal groups; 22 in each group: Group 1 (control group) received no glutamine, Group 2 received oral glutamine 0.5 g/kg/d for 5 days, and Group 3 received parenteral glutamine 0.5 g/kg/d by intravenous infusion for 5 days. All patients received glutamine-free tube feed throughout the study period. Total leukocyte count (TLC), total lymphocyte count, total protein and serum albumin, serum lactate, and sequential organ failure assessment (SOFA) score were recorded on each day for 7 days and were compared. Results: Decrease in the TLC and increase in lymphocyte count was most evident in Group 3 compared to Groups 2 and 1 which was statistically significant. Decrease in serum lactate and increase in serum protein and albumin was maximum in Group 3 compared to Groups 1 and 2 which was statistically significant. The mean duration of hospital stay of Group 3 was the least followed by Groups 2 and 1 which was statistically not significant. There was an improvement in SOFA score in all the three groups. Conclusion: Parenteral glutamine in a dose of 0.5 g/kg/d was more potent than oral glutamine in improving the biochemical parameters. The duration of hospital stay was similar in all the groups after treatment.